Frequency of Medical Claims for Diastasis Recti Abdominis Among U.S. Active Duty Service Women, 2016 to 2019 - Jessica Korona-Bailey; Amanda Banaag; Penelope Jones; Dana R. Nguyen; Tracey P?rez Koehlmoos (Mary Ann Liebert, 2023)
Background: Diastasis recti abdominis (DRA) is a condition in pregnant and postpartum women. Proposed risk factors include age, sex, multiparity, cesarean delivery, diabetes, gestational weight gain, and high birth weight. This study aims to estimate the prevalence of DRA using medical claims data among U.S. active duty service women (ADSW) and determine associated risk factors. Materials and Methods: We conducted a cross-sectional study of ADSW aged 18 years and older in the U.S. Army, Air Force, Navy, and Marine Corps during fiscal years (FYs) 2016 to 2019. Utilizing claims data, we identified ADSW with a diagnosis of DRA during the study period. Risk factors, including age, race, socioeconomic status, branch of service, military occupation, delivery type, and parity, were evaluated through descriptive statistics, chi-square tests, and logistic regression analysis. Results: A total of 340,748 ADSW were identified during FYs 2016 to 2019, of whom 2,768 (0.81%) had a medical claim for DRA. Of those with deliveries during the study period, 1.41% were multiparous and 84.53% had a cesarean delivery. Increased risk of DRA was found in ages 30 to 39 years, Black women, ranks representing a higher socioeconomic status, and women with overweight and obese body mass indices. Conclusions: Although the prevalence of DRA, defined as a medical claim for DRA, in the study population is low, subpopulations may be disproportionately affected by the condition. Further research could potentially detail the impact of DRA on the functional impairment and operational readiness of ADSW in the U.S. military and any possible means of prevention.